A review of the development and implementation of the critical source area concept: A reflection of Andrew Sharpley's role in improving water quality - McDowell, Richard; Kleinman, Peter J. A.; Haygarth, Philip; McGrath, Joshua M.; Smith, Douglas; Heathwaite, Louise; Iho, Antti; Schoumans, Oscar; Nash, David (John Wiley & Sons, 2025)
Critical source areas (CSAs) are small areas of a field, farm, or catchment that account for most contaminant loss by having both a high contaminant availability and transport potential. Most work on CSAs has focused on phosphorus (P), largely through the work in the 1990s initiated by Dr. Sharpley and colleagues who recognized the value in targeting mitigation efforts. The CSA concept has been readily grasped by scientists, farmers, and policymakers across the globe. However, experiences and success have been mixed, often caused by the variation in where and how CSAs are defined. For instance, analysis of studies from 1990 to 2023 shows that the proportion of the annual contaminant load coming from a CSA decreases from field to farm to catchment scale. This finding is consistent with increased buffering of CSAs and greater contribution of other sources with scale, or variation in the definition of CSAs. We therefore argue that the best application of CSAs to target mitigation actions should be at small areas that truly account for most contaminant loss. This article sheds light on the development and utilization of CSAs, paying tribute to Dr. Sharpley's remarkable contributions to the improvement of water quality, and reflecting upon where the CSA concept has succeeded or not in reducing contaminant (largely P) loss.
Keywords: critical source areas; contaminant loss; phosphorus; mitigation targeting; scale variability